Bidirectional Antenna for 2.4-ghz WLAN Application Inside Train - Mahyeddin, Mohd Eizzuddin; Kai, L. S.; A. Majid, Huda; A. Latif, M. F.; Padeli, M. A. (UTHM, 2020)
In this paper, a bidirectional antenna is presented for a WLAN application inside monorail train. The Yagi Uda antenna has directional characteristic that is suitable for the long path service area. The design concept of the proposed antenna has two directional antennas combined pointed in opposite direction which only involves the driven element and directors. The Yagi Uda design of bidirectional antenna operates in the frequency band of 2.4 GHz. The antenna is proposed with a thickness of 1.6mm and relative permittivity of 4.3 on FR4 substratum. Resonant frequency is set at 2.42 GHz with a bandwidth of 390 MHz from simulation work. The proposed antenna also met the estimated antenna bandwidth at a range of 2.23 GHz-2.63 GHz, and the bidirectional pattern. Both simulated and measured result are well matched.